The Mangga Bridge-Culinary Tourism Destination: Abandoned Infrastructure, Policy, and Revitalization - Ambia Arma, Nur (Indonesian Association for Public Administration (IAPA), 2024)
The development of tourism village is a mainstay of many countries which has potential because they are considered useful in improving the economy and welfare of their people. There are many papers on the development of tourism village by finding various unique attractions as different tourist features. Likewise, Indonesia has a story of revitalizing an unused bridge into a culinary tourist attraction called the Mangga Bridge. The purpose of this study is to analyze the process of revitalizing an abandoned bridge to become one of the rural culinary tourism destinations and the impact of implementing this revitalization in the context of developing a tourism village. Using descriptive qualitative methods with data collection techniques such as interviews and from documens. The collected data were then analyzed using the interactive model. We found that revitalizing an abandoned bridge is one of the strategies that can turn Namo Sialang village into a tourism village because Mangga Bridge or the bridge cafe is a culinary tourist attraction. In addition, the tourism village development policy through the revitalization of abandoned bridges has had several positive impacts: 1) Namo Sialang village can already be proposed as a tourism village because it has unique resources as a tourist attraction; 2) through the mangga bridge, the government opens jobs for the community through culinary businesses managed by village-owned enterprises (BUMDES), where this can increase people's income. 3) the government regains public trust and increases community participation in village development.